The Role of DNA Damage in Neural Plasticity in Physiology and Neurodegeneration - Konopka, Anna; Atkin, Julie D. (Frontiers in Cellular Neuroscience, 2022)
Damage to DNA is generally considered to be a harmful process associated with aging and aging-related disorders such as neurodegenerative diseases that involve the selective death of specific groups of neurons. However, recent studies have provided evidence that DNA damage and its subsequent repair are important processes in the physiology and normal function of neurons. Neurons are unique cells due to their ability to changes through growth and reorganization by forming new neural connections throughout life in response to stimuli. This ‘plasticity’ is essential for cognitive processes such as learning and memory as well as brain development, sensorial training, and recovery from brain lesions. Interestingly, recent evidence has suggested that the formation of double strand breaks (DSBs) in DNA, the most toxic form of damage, is a physiological process that modifies gene expression during normal brain activity. Together with the subsequent DNA repair, this is thought to underlie neural plasticity and thus control neuronal function. Interestingly, neurodegenerative diseases such as Alzheimer’s disease, amyotrophic lateral sclerosis, frontotemporal dementia or Huntington’s disease manifest by decline in cognitive functions, which are govern by plasticity. This suggests that DNA damage and DNA repair processes that normally function in neural plasticity can contribute to neurodegeneration. In this review we summarize our current understanding about the relationship between DNA damage and neural plasticity in physiological conditions as well as in the pathophysiology of neurodegenerative diseases.